Three-year-olds’ theories of mind in actions and words - Rhodes, Marjorie; Brandone, Amanda C. (Frontiers in Psychology, 2014)
Understanding observable behavior by considering mental representations is central to social cognition. Research reveals quite different developmental trajectories for this ability depending on whether tasks assess implicit or explicit theory of mind. Yet, how to define implicit vs. explicit theory of mind, the tasks that elicit each, and the types of behavior that each can support, have remained unclear. The present study (n = 47) found that 3-year-olds incorporate predictions based on false beliefs into their intentional actions, but not—following identical scenarios—into their verbal responses. These data show that implicit theory of mind supports a broader range of behaviors than previously indicated and further illustrates the entrenched nature of the distinction between implicit and explicit knowledge in early conceptual development.